PENGAWASAN ORANG TUA TERHADAP PENGGUNAAN MEDIA SOSIAL DI ERA 4.0 PADA REMAJA USIA SEKOLAH MENENGAH PERTAMA (SMP) DI KELURAHAN SUKARAMI KOTA BENGKULU - Permata Dinda , Kurnia (Yayasan Darussalam Bengkulu, 2022)
This research is motivated by looking at the developments in the digital era 4.0 which has skyrocketed high with the many latest technological innovations. With so many social media that have sprung up with different versions and functions. Social media has its own impact on its users, both positive and negative impacts. Teenagers today cannot be separated from the use of social media, this is certainly a very worrying thing for the future of teenagers, besides being used as a means of entertainment, there are lots of uploads that damage the morals and behavior of teenagers because various social media do not select videos. that will be uploaded, therefore parental supervision is very necessary. Based on the results of research that has been carried out there are several forms of supervision carried out by parents, namely there are 4 types, 1) Authoritative Parenting (warm and firm) parents provide supervision by providing advice for using social media properly, not getting angry so that children feel not threatened and hurt, 2) Authoritarian Parenting (less willing to accept the child's will) parents state to supervise by limiting children in using cellphones and filling in data/internet quotas, giving time limits to children when to use cellphones and when to stop using cellphones., 3 ) Neglect Parenting (little time for children) parents try to give a lot of time for children, but because the task of parents is not only at home, and children also need the outside world, playing with their friends, we as parents simply give a time limit only, so that children do not lose track of time, 4) Indulgent Parenting (giving high freedom to children) people parents supervise by limiting children's use of cellphones and charging data/internet quotas, giving time limits to children when to use cellphones and when to stop using cellphones.